2021
DOI: 10.1111/os.12936
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐ to Long‐Term Outcomes of Cementless Modular, Fluted, Tapered Stem for Massive Femoral Bone Loss in Revision Total Hip Arthroplasty

Abstract: Objective To evaluate mid‐ to long‐term results of revision total hip arthroplasty for massive femoral bone loss using a cementless modular, fluted, tapered stem. Methods This is a retrospective study performed at a single hospital. During the period of January 2007 to January 2015, 33 patients (34 hips) underwent primary revision surgery with cementless modular, fluted, tapered stems due to femoral bone loss. Sixteen men and 17 women were included in the study, with an average age of 63.9 ± 11.7 years (range,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Among the various parameters considered, the only association that could be established was with Dorr type C femurs and the use of structural grafts, both related to bone loss severity ( 30 ). In this review, 7 out of 15 studies reported a subsidence ( 19 , 20 , 22 , 26 - 28 , 31 ), with an average of 4.2 mm (SD, ±4.05 mm). Stem subsidence greater than 5 mm was reported only in 34/648 of cases, 5% of the total.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Among the various parameters considered, the only association that could be established was with Dorr type C femurs and the use of structural grafts, both related to bone loss severity ( 30 ). In this review, 7 out of 15 studies reported a subsidence ( 19 , 20 , 22 , 26 - 28 , 31 ), with an average of 4.2 mm (SD, ±4.05 mm). Stem subsidence greater than 5 mm was reported only in 34/648 of cases, 5% of the total.…”
Section: Resultsmentioning
confidence: 89%
“…Interestingly, the highest number of dislocations has been reported by Wirtz (n=20, 12%), who reported being in line with the published literature at that time ( 25 ). Considering only studies produced in the last 5 years ( 19 , 20 , 22 , 26 , 27 ), the overall dislocation rate drops to 2.6% (SD, ±2.7%). This difference can be hypothetically attributed to surgical techniques and tribology improvements, like the introduction of 36 mm heads and dual mobility couplings.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Few studies with limited samples have analysed a single type of implant in a heterogeneous patient and surgical population for MFT stems. 4,6,[19][20][21][22][23][24][25][26] Survival of different MFTs varies minimally according to the type of implant used. On the other hand, while survival is often satisfactory, implant fractures may have negatively impacted the reputation of these modular implants.…”
Section: Discussionmentioning
confidence: 99%
“…Subsidence of the stem has shown to be a negative predictive sign for successful osseointegration and was also considered to be one of the most common risk factors for re-revision, whereby the importance and extent of subsidence varies by implant design [ 16 , 20 , 21 ]. Furthermore, the reason for revision can also be associated with an increased risk of subsidence.…”
Section: Discussionmentioning
confidence: 99%